2013
DOI: 10.1002/tea.21101
|View full text |Cite
|
Sign up to set email alerts
|

Systemizing: A cross‐cultural constant for motivation to learn science

Abstract: The present study is based on the empathizing‐systemizing (E‐S) theory of cognitive science. It was hypothesized that the influence of students' gender on their motivation to learn science is often overestimated in the research literature and that cognitive style is more important for motivation than students' gender. By using structural equation modeling, and based on previous research, a precise causal model was formulated to test this hypothesis. Then, using multiple group confirmatory analysis, the model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 77 publications
2
24
0
2
Order By: Relevance
“…As expected, the results of the SEM analyses provided support for all study hypotheses. Consistent with past research (Zeyer et al 2012(Zeyer et al , 2013, systemizing positively predicted intrinsic motivation. As such, high systemizers reported feeling more intrinsically motivated to study science compared to low systemizers.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As expected, the results of the SEM analyses provided support for all study hypotheses. Consistent with past research (Zeyer et al 2012(Zeyer et al , 2013, systemizing positively predicted intrinsic motivation. As such, high systemizers reported feeling more intrinsically motivated to study science compared to low systemizers.…”
Section: Discussionsupporting
confidence: 87%
“…It implies that systemizers will be motivated to study subjects like science, and empathizers will be motivated to pursue people-centered fields. Indeed, previous studies (Zeyer et al 2013;Zeyer et al 2012) found significant positive correlations between systemizing and motivation to learn science as measured by the Science Motivation Questionnaire (SMQ; Glynn and Koballa 2006), which includes intrinsic and extrinsic items. It is probable that low systemizers will not enjoy studying science.…”
Section: Self-determination Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on students' learning motivation have employed the SMQ. The reason is that, while other motivation assessment instruments deal with some specific motivation elements such as efficacy or interest, the SMQ is capable of assessing many key components with just one single set (Zeyer et al, 2013). In addition, there are already many preceding studies employing SMQ (Bryan et al, 2011;Glynn et al, 2009Glynn et al, , 2011Ha & Lee, 2012;Salta & Koulougliotis, 2015;Tosun, 2013), to compare with this present study finding.…”
Section: Instrumentmentioning
confidence: 55%
“…While some STEM researchers have called for sensitivity to diversity, equality and cultural concerns in STEM programme evaluation 38,39 the majority of STEM programmes do not consider these elements to be important type. Participant satisfaction surveys were used to measure twinning quality.…”
Section: Programme Theory For the Children And Schools Programmementioning
confidence: 99%